1989
DOI: 10.1128/mcb.9.5.2202
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression in male and female mouse liver of very similar mRNAs specified by two group 1 major urinary protein genes.

Abstract: The major urinary proteins of the mouse are encoded by a large multigene family composed of several distinct groups of genes distinguished by differences in sequence and expression characteristics. The genes in the largest group (group 1) show greater than 99% pairwise similarity in their exons. By hybridization between RNA and a specifically designed oligonucleotide, we confirmed that genes of this group are expressed mainly in the liver. By using additional gene-specific oligonucleotide probes, we have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…The lower serum levels of IGF-I observed in neuroDrd2KO mice are consistent with their smaller body size and weight, a phenotype that in the wild could be detrimental for reproductive fitness due to reduced competitiveness among males. The sexually dimorphic liver proteins that depend on the male pattern of GH release is manifold and include MUPs (McIntosh and Bishop, 1989). This group of pheromones secreted into the blood and then excreted in the urine are known to promote social recognition and territorial dominance between males (Hurst et al, 2001;Chamero et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The lower serum levels of IGF-I observed in neuroDrd2KO mice are consistent with their smaller body size and weight, a phenotype that in the wild could be detrimental for reproductive fitness due to reduced competitiveness among males. The sexually dimorphic liver proteins that depend on the male pattern of GH release is manifold and include MUPs (McIntosh and Bishop, 1989). This group of pheromones secreted into the blood and then excreted in the urine are known to promote social recognition and territorial dominance between males (Hurst et al, 2001;Chamero et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although other sexually differentiated hepatic transcripts have been shown to be regulated in the mouse by the difference in GH-release pattern, the dependence on the mode of GH administration is either partial (34,35) or more complex (14,26) than in the case of C4/C4-Slp. In our opinion, the genetic complexity of the other systems in contrast to C4/C4-Slp must be responsible for the incomplete down-regulation of Mup by GH (35), for the peculiar multihormonal regulation (i.e., by estrogens, thyroid, and glucorticoid hormones) of the P-450 II family (reviewed in ref.…”
Section: C4-slp Can Be Expressed In the Absence Of Tetosteronementioning
confidence: 99%
“…As in other mammals, C4 is produced both in liver and in macrophages, but only hepatocytes synthesize Slp. Even though other hepatic genes that display sexually dimorphic regulation have been more intensively studied (9, 10), the C4/C4-Slp system is notable for its more pronounced testosterone response, the array of available regulation variants (11), and lack of the genetic and functional complexity seen in multigene families such as the androgen-inducible a2u globulin in the rat (12) and the homologous mouse major urinary protein (Mup) (13,14). The system acquires additional interest by the existence of trans-acting mutations (15, 37) that override the testosterone requirement of the C4-Slp gene.…”
mentioning
confidence: 99%
“…We found that the mRNA level of mouse major urinary protein-1 (MUP-1) 2 was markedly down-regulated in db/db mice, and the change was largely normalized upon treatment with the PPAR␄ agonist rosiglitazone. MUP-1 is a small molecular weight secreted protein abundantly expressed in the liver (14). Its expression in the liver is enhanced by administration of the hepatotoxic agent dimethylnitrosamine (15) …”
mentioning
confidence: 99%